Analysis of Incorporation of Ion-Bombarded Nickel Ions with Silicon Nanocrystals for Microphotonic Devices. (16th August 2022) - Natrayan, L.; Kumar, P. V. Arul; Kaliappan, S.; Sekar, S.; Patil, Pravin P.; Jayashri, R.; Esakki Raj, E. S.
Abstract : Nanotechnology is playing a greater role in biomedical engineering. Microphotonic technology is on another side, having faster growth with more requirements. The nanocrystals are a part of nanotechnology which uses silicon for manufacturing. These silicon nanocrystals have the optical property mostly used in microphotonic devices. Silicon nanocrystals are of biocompatibility with less toxicity. Therefore, the advancement in the silicon nanocrystal helps develop more microphotonic devices for biological purposes. One critical factor of silicon nanocrystal is the surface defects or surface imperfections. Surface passivation is the method employed for rectifying this disadvantage of silicon nanocrystal. Another major thing is that silicon nanocrystals are size dependent. So proper variation on the surface is required for yielding high performance of the nanocrystal. After characterizing the surface of the silicon nanocrystal, ion bombardment can occur. Nickel is a lustrous white chemical element which is less reactive when it is of a smaller size. So ion bombardment of nickel ion on the surface of the silicon nanocrystal can be done to improvise the performance of the microphotonic devices. Nearly there is an excess of 20 a.u. of photoluminescence intensity yielded. The relative fluorescence is also increased by 150 a.u. This research work enhanced the silicon nanocrystal using ion bombardment of nickel ion, which increased energy traps resulting in more intensities.